การปฏิบัติการเฝ้าระวังการติดเชื้อตำแหน่งผ่าตัดและปัจจัยที่เกี่ยวข้องของโรงพยาบาลเอกชน - กัญญ์นิฏฐา วงษ์ศิริ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Effective surgical site infection (SSI) surveillance practices are key to preventing SSIs. This descriptive study aimed to study the SSI surveillance practices and related factors at private hospitals from September 2014 to January 2015. The sample was 69 healthcare personnel (infection control nurses or key persons responsible for SSI surveillance) in private hospitals. Research instruments employed in this study were a demographic questionnaire, a hospital information questionnaire, a surveillance practices questionnaire, and the SSI surveillance related factors questionnaire. Data were analyzed using descriptive statistics. The study found that most SSI data collection and recording were performed by infection control nurses (73.91%). The Centers for Disease Control and Prevention (CDC) definition was used to diagnose SSIs accounting for 59.42%. Fifty-seven point ninety-seven percent of study hospitals performed SSI surveillance for all types of surgery. SSIs were diagnosed by the surgeons 79.7% of the time. The SSI rate was computed by the number of SSIs divided by the total number of operations in each procedure multiplied by 100 and accounted for 66.67%. The SSI rates were reported monthly to the related staff accounting for 75.36%, and reported to the Infection Control Committee accounting for 60.87%. Post-discharge surveillance could include 84.06% of patients after surgery and SSI surveillance practices included 15.90% of hospitals had SSI surveillance efficiency rates of 100%. The related factors to SSI surveillance practices were divided into three domains and were comprised of: 1) structure: private hospitals had full-time infection control personnel 73.9%; 2) process: 59.42% of hospitals provided training in SSI prevention for novice staff and 68.12% held an annual refresher course for current staff; and 3) outcomes: the data from the surveillance were used in SSI prevention planning accounting for 82.61%. However, problems in SSI surveillance practices included 14.28% of hospitals had SSI surveillance efficiency rates of less than 60%. These hospitals required support for SSI surveillance practices. Study participants noted that support needed included collaboration from colleagues (94.20%) and hospital administrators (71.01%), and adequate staffing (52.17%). The findings suggest that most private hospitals have standard SSI surveillance practices. However, some practices are diverse among hospitals. This information can be used to make a development plan for SSI surveillance practices in private hospitals. It may lead to the establishment of an SSI surveillance database for private hospitals in Thailand.